2003
DOI: 10.1248/bpb.26.1283
|View full text |Cite
|
Sign up to set email alerts
|

Antinociceptive Profiles of Crude Extract from Roots of Angelica gigas NAKAI in Various Pain Models

Abstract: To characterize the antinociceptive profiles of Angelica gigas NAKAI (ANG; Korean angelica), methanol extract from the dried roots of ANG was made and mice were administered orally at the various doses (from 0.25 to 3 g/kg). ANG produced the increased latencies of the tail-flick and hot-plate paw-licking responses in a dose-dependent manner. In acetic acid-induced writhing test, ANG dose-dependently decreased writhing numbers. Moreover, the cumulative response time of nociceptive behaviors induced by intraplan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
27
1

Year Published

2005
2005
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(30 citation statements)
references
References 22 publications
(20 reference statements)
2
27
1
Order By: Relevance
“…In addition, decursin, a major coumarin derivative, greatly improved scopolamine-induced amnesia in both passive avoidance and Morris water maze performance tests through AChE inhibition in vivo (Kang et al, 2003). It was also recently reported that coumarins and/or extract of A. gigas exhibited anti-amnesic (Yan et al, 2004), antitumor , antinociceptive (Choi et al, 2003), anti-bacterial and antiplatelet aggregation (Lee et al, 2003d) activities. In order to obtain a more effective remedy for the treatment of memory deficiency than exclusively using A. gigas roots, we combined several extracts of Oriental herbs and changed the composition based on both traditional references and the results of our previous work.…”
Section: Introductionmentioning
confidence: 92%
“…In addition, decursin, a major coumarin derivative, greatly improved scopolamine-induced amnesia in both passive avoidance and Morris water maze performance tests through AChE inhibition in vivo (Kang et al, 2003). It was also recently reported that coumarins and/or extract of A. gigas exhibited anti-amnesic (Yan et al, 2004), antitumor , antinociceptive (Choi et al, 2003), anti-bacterial and antiplatelet aggregation (Lee et al, 2003d) activities. In order to obtain a more effective remedy for the treatment of memory deficiency than exclusively using A. gigas roots, we combined several extracts of Oriental herbs and changed the composition based on both traditional references and the results of our previous work.…”
Section: Introductionmentioning
confidence: 92%
“…The anti-inflammatory properties of Achyranthis Radix (Ida et al, 1998), Atractylodis Rhizoma (Resch et al, 1998) Cinnamomi Cortex Spissus (Hong et al, 2002), Glycyrrhizae Radix (Baltina, 2003), Poria cocos (Schinella et al, 2002), Paeoniae Radix (Xue et al, 2000), Rehmanniae Radix Preparata (Kim et al, 1999), and Zingiber officinale (Shen et al, 2003) have been mentioned. The analgesic properties of Angelicae Gigantis Radix (Choi et al, 2003), and Eucommiae Cortex (Hong et al, 1988) were earlier investigated in various inflammatory pain models. Therefore, these results suggest that CML-1 may have synergic therapeutic effects from each herb on inflammatory diseases.…”
Section: Introductionmentioning
confidence: 99%
“…The extraction method was modified from the article of Choi et al (2003). Crude extract was prepared as follow.…”
Section: Preparation Of Crude Extraction From Leaves and Stalks Of Anmentioning
confidence: 99%